Effect of interspecific competition on trait variation in Phaeobacter inhibens biofilms - Lutz, Carla (2018)
Interspecific competition between bacteria shapes community dynamics, causing evolutionary changes that affect life history traits. Here, we studied the role of interspecific competition on the generation of trait diversity using a two-species model system of marine, surface-associated bacteria. Bacterial biofilms of Phaeobacter inhibens were established alone or in competition with Pseudoalteromonas tunicata and phenotypic traits of dispersal cells were assessed during biofilm development. P. inhibens dispersal isolates from competition biofilms displayed less phenotypic variation, were superior competitors, were less susceptible to predation, and reached higher planktonic biomass than isolates from noncompetition biofilms. Moreover, the maintenance of competitive ability exhibited by individual dispersal isolates from competition biofilms did not result in an obvious reduction (measured as a negative trait correlation) in other traits, but was rather positively correlated with planktonic growth. However, where negative correlations between traits were found, they were exhibited by individuals derived from noncompetitive biofilms, whose populations also had a higher degree of trait variation than those from biofilms experiencing competition. Our observations indicate that interspecific competition during biofilm formation is important for maintaining both competitive ability and affects variation in ecologically relevant traits. Given that most bacteria in biofilms exist in diverse, multispecies communities, an understanding of how bacteria respond to biotic factors such as interspecific competition is critical for understanding the dynamics of bacterial populations in both ecological and evolutionary time.